Determination of The Parents Based on Molecular Analysis for Soybean Lines Development - Slamet Slamet; Nonon Saribanon; Saptowo Jumali Pardal; Tatang Mitra Setia; Wening Enggarini; Reflinur Reflinur (JURNAL SAINS NATURAL, 2022)
Soybean is the third most important food commodity in Indonesia, which is a cheap source of protein and rich in different nutritional contents for humans. This study aimed to analyze the four genotypes of the crossing parents using SSR primers and select one SSR polymorphic primer to confirm the F1 generation alleles compared to their parents. The research was conducted in the laboratory and greenhouse of the Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development (ICABIOGRAD). The research activities included a polymorphic primers survey, population formation, and confirmation of crossing populations using one polymorphic primer. A total of 20 SSR primers were used to amplify the DNA of the four crossing parents (Biosoy 1, Biosoy 2, Demas, and Tanggamus). The results of the polymorphic SSR survey showed that 6 SSR primers could distinguish the combination of Biosoy 2 vs Demas parents, then 7 SSR primers could distinguish the combination of Biosoy 1 vs Tanggamus and Biosoy 2 vs Tanggamus parents. Satt 406 polymorphic primer was chosen to analyze F1 hybrid lines of three crossings. Based on phenotypic observation, two individuals were suspected to be hybrid lines. Molecular analysis using Satt 406 showed that alleles from male parents were not found in 16 F1 individuals from the three crossings. Selection using molecular markers such as Satt 406 polymorphic SSR can help breeders screen heterozygous populations in F1 generations to check successful crossings.Keywords: biosoy 1; biosoy 2; Demas; Tanggamus; Al tolerance; SSR markers ABSTRAKPenentuan Tetua Berbasis Analisis Molekuler Untuk Pembentukan Galur KedelaiKedelai merupakan komoditas pangan penting ketiga di Indonesia yang dimanfaatkan sebagai sumber protein yang murah dan kaya berbagai kandungan gizi bagi manusia. Tujuan penelitian ini adalah untuk untuk menganalisis 4 genotip tetua persilangan menggunakan primer SSR dan memilih satu primer polimorfik SSR untuk mengonfirmasi alel-alel generasi F1 dibandingkan dengan para tetuanya. Penelitian dilakukan di laboratorium dan rumah kaca Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian (BB Biogen). Kegiatan penelitian terdiri dari survei primer polimorfik, pembentukan populasi, dan konfirmasi populasi persilangan menggunakan satu primer polimorfik. Sebanyak 20 primer SSR digunakan untuk mengamplifikasi DNA dari empat tetua persilangan kedelai (Biosoy 1, Biosoy 2, Demas, dan Tanggamus). Hasil survei polimorfisme SSR menunjukkan bahwa 6 primer SSR dapat membedakan kombinasi tetua Biosoy 2 vs Demas, serta 7 primer SSR dapat membedakan Biosoy 1 vs Tanggamus dan Biosoy 2 vs Tanggamus. Primer polimorfik Satt 406 terpilih untuk menganalisis hibrida F1 dari tiga persilangan. Berdasarkan hasil pengamatan fenotipik, diperoleh 2 nomor individu F1 yang diduga sebagai generasi hibrida. Analisis molekuler menggunakan Satt 406 menunjukkan bahwa alel-alel dari tetua jantan tidak ditemukan pada 16 nomor tanaman dari 3 populasi  persilangan. Seleksi menggunakan marka molekuler seperti SSR polimorfik Satt 406 membantu pemulia dalam menskrining populasi heterozigot pada generasi F1 untuk mengetahui keberhasilan persilangan.Kata kunci: biosoy 1, biosoy 2, Demas, Tanggamus, toleransi Al, marka SSR